EKSISTENSI PEREMPUAN DALAM KURSI KEPEMIMPINAN DALAM AL-QUR’AN: APLIKASI TEORI BATAS HUKUM TUHAN ( ḤUDŪD) MUHAMMAD SYAHRUR - Afrida Arinal Muna (Marwah: Jurnal Perempuan, Agama dan Jender, 2020)
Discussion about the existence of women in the public sphere is still a matter that invites debate. This is due to the many discourse that develops in the community. The discourse influences one's thinking in seeing women who come down in the public sphere, especially occupying leadership spaces. Therefore, the writer wants to see how this issue is seen in Muhammad Syahrur's discourse using his boundary theory. This Syahrur's thought was different from the thought of the classical scholars who tended to be too 'textualist' in looking at the text. They are of the view that universal Islam is Islam that existed at the time of the Prophet. Syahrur also considered the different contexts of space and time as when the na'al of the Qur'an was revealed.